Management appropriateness and outcomes of patients with acute pulmonary embolism. Issue 5 (10th May 2018) - Jiménez, David; Bikdeli, Behnood; Barrios, Deisy; Morillo, Raquel; Nieto, Rosa; Guerassimova, Ina; Muriel, Alfonso; Jara-Palomares, Luis; Moores, Lisa; Tapson, Victor; Yusen, Roger D.; Monreal, Manuel
The impact of adherence to published guidelines on the outcomes of patients with acute pulmonary embolism (PE) has not been well defined by previous studies. In this prospective cohort study of patients admitted to a respiratory department (n=2096), we evaluated whether patients with PE had better outcomes if they were acutely managed according to international guidelines. Outcomes consisted of all-cause mortality, PE-related mortality, recurrent venous thromboembolism (VTE) and major bleeding events during the first month of follow-up after diagnosis. Overall, 408 patients (19% (95% CI 18–21%)) did not receive guideline-adherent PE management. Patients receiving non-adherent management were significantly more likely to experience all-cause mortality (adjusted odds ratio (OR) 2.39 (95% CI 1.57–3.61) or PE-related mortality (adjusted OR 5.02 (95% CI 2.42–10.42); p<0.001) during follow-up. Non-adherent management was also a significant independent predictor of recurrent VTE (OR 2.19 (95% CI 1.11–4.32); p=0.03) and major bleeding (OR 2.65 (95% CI 1.66–4.24); p<0.001). An external validation cohort of 34 380 patients with PE from the RIETE registry confirmed these findings. PE management that does not adhere to guidelines for indications related to anticoagulation, thrombolytics and inferior vena cava filters is associated with worse patient outcomes. Management that does not adhere to guidelines is associated with worse outcomes in patients with acute PE http://ow.ly/vxvu30jkKuM